PENGARUH PROFITABILITAS, INTENSITAS ASET TETAP, DAN PERTUMBUHAN PENJUALAN TERHADAP PENGHINDARAN PAJAK SAAT PANDEMI COVID-19 - Ismayanti Ananda Putri; Siska; Yolanda Pratami (Journal Of Islamic Finance And Accounting Research, 2022)
Tax avoidance is an attempt to reduce the tax burden but does not violate the applicable tax regulations. This study aims to examine and analyze the effect of profitability variables, fixed asset intensity, and sales growth on tax avoidance during the Covid-19 pandemic. This research includes quantitative research with an associative approach that uses secondary data in the form of quarterly financial reports I, II, and III. The population in this study were 47 large trading companies (wholesale: durable and non-durable goods) listed on the IDX in 2020. The research sample was selected using the purposive sampling method so that 18 companies were obtained over a span of 3 quarters in 2020. Data analysis used the technique multiple linear regression analysis. Based on the results of the tests that have been carried out, it shows that partially the profitability and sales growth variables have no significant effect on tax avoidance during the Covid-19 pandemic, while the fixed asset intensity variable has a significant effect on tax avoidance during the Covid-19 pandemic. Simultaneously, profitability variables, fixed asset intensity, and sales growth have a significant effect on tax avoidance during the Covid-19 pandemic.